2000
DOI: 10.1007/s000180050506
|View full text |Cite
|
Sign up to set email alerts
|

Decreased monosaccharide transport in renal brush-border membrane vesicles of spontaneously hypertensive rats

Abstract: Na(+)-dependent D-glucose and D-galactose transport were studied in brush-border membrane vesicles (BBMVs) from kidney cortex isolated from both spontaneously hypertensive rats (SHR) and their normotensive genetic control Wistar-Kyoto (WKY) rats. Initial rates and accumulation ratios of Na(+)-dependent D-glucose and D-galactose transport were significantly lower in SHR compared with WKY, the observed decreases being similar for both substrates. To explain the reduction in sugar transport by renal BBMVs, the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…This study demonstrates that the expression of SGLT2 was not modified in chronic NOS-inhibited hypertensive animals, therefore suggesting that SGLT2 activity is altered in this experimental model. In agreement with these results, Mate et al[ 42] reported a decrease in Na + -glucose uptake in renal BBV from spontaneously hypertensive rats (SHR) compared with control Wistar Kyoto rats. In contrast, Bautista et al [18] described an increase in Na + -dependent D -glucose uptake in renal BBV isolated from rats made hypertensive by aortic coarctation.…”
Section: Discussionsupporting
confidence: 74%
“…This study demonstrates that the expression of SGLT2 was not modified in chronic NOS-inhibited hypertensive animals, therefore suggesting that SGLT2 activity is altered in this experimental model. In agreement with these results, Mate et al[ 42] reported a decrease in Na + -glucose uptake in renal BBV from spontaneously hypertensive rats (SHR) compared with control Wistar Kyoto rats. In contrast, Bautista et al [18] described an increase in Na + -dependent D -glucose uptake in renal BBV isolated from rats made hypertensive by aortic coarctation.…”
Section: Discussionsupporting
confidence: 74%
“…In fact, it was recently found that the Na ϩ -dependent D-glucose transport in SHR kidney cortex was significantly lower than in WKY, this being accompanied by similar decreases in the expression of the phlorizin-sensitive D-glucose transporter (31). By contrast, Na ϩ uptake, studied using 22 Na ϩ , was significantly increased in SHR (31). This fits well with the evidence that the hypertensive effect of HS intake on animal models with a diminished renal capacity to excrete salt, such as the SHR (1,4,46), may result from a combination of excessive salt intake and reduced salt excretion (62).…”
Section: Discussionmentioning
confidence: 92%
“…Since increases in blood pressure in hypertensive subjects appear to be linked to an altered Na ϩ transport across the tubular epithelium, as evidenced by increases in the activity of Na ϩ -K ϩ -ATPase (10, 13), type 3 Na ϩ /H ϩ exchanger (NHE3) (29,35,63), and Cl Ϫ /HCO 3 Ϫ exchanger (36), it is likely that in hypertension changes in the Na ϩ transport across the renal tubular epithelium may also affect the Na ϩ -dependent transport of amino acids. In fact, it was recently found that the Na ϩ -dependent D-glucose transport in SHR kidney cortex was significantly lower than in WKY, this being accompanied by similar decreases in the expression of the phlorizin-sensitive D-glucose transporter (31). By contrast, Na ϩ uptake, studied using 22 Na ϩ , was significantly increased in SHR (31).…”
Section: Discussionmentioning
confidence: 94%
“…Renal cortical BBMVs were prepared from SHR and WKY by a MgCl 2 precipitation method, as previously described in detail [11]. The final pellets containing purified BBMVs were resuspended in the buffers used in transport experiments, whose compositions are reported in uptake studies, and homogenized with a 25-and 29-gauge needle.…”
Section: Preparation Of Bbmvsmentioning
confidence: 99%
“…SGLTs [11]. However, whether the observed changes in the renal transport of D-glucose and D-galactose in hypertensive rats are specific for an Na + -dependent sugar cotransporter or whether other sugar transporters, such as GLUT5, are also affected in the kidney of hypertensive rats is unknown.…”
mentioning
confidence: 98%